Human existence potential in Europe during the Last Glacial Maximum. (20th April 2021) - Klein, Konstantin; Wegener, Christian; Schmidt, Isabell; Rostami, Masoud; Ludwig, Patrick; Ulbrich, Sven; Richter, Jürgen; Weniger, Gerd-Christian; Shao, Yaping
Abstract: Archaeological records indicate that many regions in Europe remained unoccupied by hunter-gatherers during the Last Glacial Maximum (LGM), probably due to the harsh climatic conditions and glacial extent. In the populated regions of southwestern Europe, a new technocomplex, the Solutrean, is known to have emerged among hunter-gatherers but did not reach the regions east of 10°E. To better understand human occupation of Europe during the LGM, Human Existence Potential (HEP) is presented, which expresses the suitability of a region with given environmental conditions for habitation by hunter-gatherers. We estimate the HEP based on archaeological site locations and reconstructed climate/environment data. By geostatistically upscaling archaeological site distributions into Core Areas, we distinguish areas that were likely to have been continuously occupied by hunter-gatherers from areas intermittently occupied. The use of Core Areas in the model improves the description of regions of continuous human presence, removing some of the previously observed mismatches between reconstructions and archaeological records. Using HEP, important anthropological and archaeological questions can be studied. Environmental Human Catchment (EHC) and Best Potential Path (BPP) are applied to quantify an area of HEP attraction and the lowest-cost path between two areas, respectively. With these tools, we characterize the potential connections between the Core Areas, the environmental barriers and possible social and technological interactions. A clear difference in environmental adaptation is found between the populations in western and eastern Europe, with a significant climate barrier preventing the propagation of the Solutrean to eastern Europe.